Non-formal Education Facilitators Perceived Impact of Training the Trainers on Teaching at the Right Level Achievements in Borno State Nigeria - Shettima, Goni; Suleina, Mohammed; Chechet, Mercy; Dadi, Mwada Nggada (Kashere Journal of Education, 2025)
This study assessed the perceived impact of the Teaching at the Right Level (TaRL) training on non-formal education facilitators in Borno State, Nigeria. The objectives of the study were to identify the training level of Non-formal facilitators in Borno State, identify how facilitators perceived TaRL in Borno State, and identify the impact of TaRL to Non formal education facilitators in Borno state. A survey was used to gather information from a random group of 200 facilitators through a structured questionnaire called "Non-formal Education Facilitators Perceived Impact of Training the Trainers" (NFEFPITT). " Descriptive statistics (frequencies and percentages) were used to analyse the data. The results showed that the first workshop was very successful, with 80% of participants saying they improved their teaching skills, 77.5% gaining skills in assessment, and 75% learning practical methods, but there was a significant issue. Only 50% of facilitators received adequate follow-up mentorship, and an overwhelming 85% expressed a high need for further training to sustain the approach. Facilitators' perceptions of TaRL were overwhelmingly positive: 85% found it effective for improving learning outcomes, and 77.5% observed increased learner engagement. However, we noted a disconnect, with only 55% receiving adequate support from programme administrators. Despite this, 82.5% would highly recommend TaRL to peers. The impact on facilitators was profound, creating a virtuous cycle. 90% observed significant improvements in learners' literacy and numeracy skills, which in turn fuelled their own professional growth; 85% reported increased confidence and enhanced teaching skills; 87.5% acknowledged contributions to their professional development; and 82.5% experienced higher job motivation and satisfaction. In conclusion, the "Training of Trainers" model effectively cultivates foundational skills and secures substantial facilitator commitment; however, it necessitates a comprehensive framework for ongoing professional development and administrative support to guarantee the enduring sustainability and scalability of TaRL accomplishments in Borno State. Recommendations include institutionalizing structured mentorship and regular refresher training